If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -7 = 6y + 13 Reorder the terms: -7 + 7y = 6y + 13 Reorder the terms: -7 + 7y = 13 + 6y Solving -7 + 7y = 13 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -7 + 7y + -6y = 13 + 6y + -6y Combine like terms: 7y + -6y = 1y -7 + 1y = 13 + 6y + -6y Combine like terms: 6y + -6y = 0 -7 + 1y = 13 + 0 -7 + 1y = 13 Add '7' to each side of the equation. -7 + 7 + 1y = 13 + 7 Combine like terms: -7 + 7 = 0 0 + 1y = 13 + 7 1y = 13 + 7 Combine like terms: 13 + 7 = 20 1y = 20 Divide each side by '1'. y = 20 Simplifying y = 20
| 18-4k=-10-k | | -14=2x+-24 | | (3k+4)x-(2k-6)y=-10 | | 4a-8=8a-(4a+8) | | 2n+18=3n+37 | | x^2-14x+360=0 | | -10(10n-9)+6(-5n+7)= | | 310=3x-8(8x+7) | | 2(x+1)-1=11 | | c=38.34+0.50 | | 5x-2(x-3)=4x+15 | | 11d-10=6d | | N-6n= | | 4m^2n+(-m^2n)=0 | | 4m^2n+(-m^2n)= | | 0.1*x+0.25(5x)=5.25 | | log=0.45 | | 0.85x=612 | | (6x-10)+(6x+10)=18 | | 5(7x+1)=5+2x | | 2(x-7)+3x-1=4x+3 | | 2x+x+9x=3+35+2-4 | | 87b+17b= | | 20x-5x+4=15x-4 | | 25t=25t+5 | | 3x-a=b+a | | -81r+73r= | | g(x)=x^2+22x+12 | | 8x+5=2x-5 | | 7x+6=-12 | | 6a^2+19a+15= | | Y+z=108 |